Comparison of visually estimated blood loss with direct hemoglobin measurement in multilevel spine surgery. Issue 11 (26th February 2013) - Guinn, Nicole R.; Broomer, Bob W.; White, William; Richardson, William; Hill, Steven E.
<x xml:space="preserve">Abstract</x> Background Estimates of blood loss in the operating room are typically performed as a visual assessment by providers, despite multiple studies showing this to be inaccurate. Use of a less subjective measurement of blood loss such as direct measurement of the hemoglobin (Hb) mass lost from the surgical field may better quantify surgical bleeding. The objective of this investigation was to compare anesthesiologist estimates of intraoperative blood loss with measured Hb loss. Study Design and Methods Sixty patients undergoing posterior spine surgery were enrolled in a prospective, randomized trial comparing intraoperative blood loss using unipolar cautery alone or with use of a bipolar tissue sealant device. Hb concentration and fluid volume were measured from all surgical sponges, suction canisters, and the cell salvage device. Using the volume and concentration of Hb from each solution allowed calculation of Hb mass, which was converted into volume of blood lost and compared with estimates of blood loss documented by the anesthesia team. A single‐sample t test of no difference was used to compare estimated with measured blood loss. Results Mean estimated blood loss exceeded measured blood loss by 246 mL (860 mL vs. 614 mL, p < 0.0001). Conclusion Estimated blood loss exceeded measured blood loss by 40% on average. The likely etiology of this discrepancy relates to the inability to visually determine Hb concentration of sanguineous solutions in suction canisters and surgical sponges. Ramifications of excessive bleeding estimates include unnecessary transfusion and overadministration of intravenous fluids, both of which may have deleterious effects.